Structural, thermal, vibrational, and optical characterization of Sn–S–Se dichalcogenide system synthesized by high-energy ball milling - de Oliveira Melquiades, Miécio [UNESP] (2021)
Layered tin-based SnS2, Sn(S0.5Se0.5)2, and SnSe2 dichalcogenide semiconductors were synthesized using high-energy ball milling. Structural analyses revealed anisotropic nanostructures with the 2H-polytype. The extended milling time produced nanocrystallites due to the high density of defects and texture indexes. A significant microstrain reduction was achieved by replacing the 1d site with heavier chalcogenides. The presence of microstrained nanocrystallites widens and redshifts the A1g and Eg Raman modes. The redshift effect also occurs when the lattice parameters are increased via doping. The overall exothermic DSC profile exhibited a subtle modification above 450 °C suggestive of SnO2 nucleation. A composition-dependent exciton redshift in UV–Vis was followed by a reduction in the band gap toward lower averaged ionic radii in the 1d site. Multiple straight-line segments in Tauc plots indicate sub-bands as a result of the multilayered structure.